DC and Low‐Frequency Electric Field Measurements on the Parker Solar Probe. Issue 9 (25th August 2020) - Mozer, F. S.; Agapitov, O. V.; Bale, S. D.; Bonnell, J. W.; Bowen, T. A.; Vasko, I.
Abstract: The Parker Solar Probe successfully makes electric field measurements over the frequency range of DC‐100 Hz, thanks to the remarkable symmetry of the antennas with respect to sunlight and the mostly radial magnetic field. Calibration of the electric field measurement is described. Sampled electric and magnetic field data are utilized to determine wave modes of whistlers and Alfven‐ion‐cyclotron waves. In the course of such determinations, the electric field effective antenna length was found to vary with frequency from 1 m at low frequencies to essentially the antenna half‐geometric length of 3.5 m above 20 Hz. Properties of the low‐frequency electric field power as functions of frequency and radial distance are determined. There is a plateau in the electric field power spectrum above 10 Hz, which is due to the power in waves exceeding the turbulent cascade power above that frequency. This wave power decreases by one to two orders of magnitude from 35 to 50 solar radii. Key Points: DC and low‐frequency electric fields have been measured near the sun. The 100‐Hz wave power decreases between 35 and 50 solar radii MHD and whistler waves are identified by combined electric and magnetic field measurements The E‐field effective antenna length increases with frequency to become the expected value for frequencies greater than about 20 Hz